Haploperla choui sp. n. (Plecoptera: Chloroperlidae), a remarkable new stonefly from Qinling Mountains of China - Li, Weihai; Yao, Gang; Qin, Xuefeng (Zootaxa, 2013)
A new chloroperline stonefly species, Haploperla choui from the Qinling Mountains, Shaanxi Province, China is de-scribed. It is compared to other species of the genus known from Asia.